Knowledge of Values and Critique of I. Kant’s Conception or A Priori in M. Scheler’s Ethics - Anilionytė, Loreta (Problemos, 1994)
The article deals with the problem of the knowledge of values in M. Scheler’s ethics. M. Scheler’s conception of material a priori, involving the principles of emotional intuition and love, is analysed in its confrontation to I. Kant’s conception of formal a priori. However, it is stated that the intention to consider emotionality as the center of ethics leads the conception to inner contradictions and leaves many questions open.